Sustainable management of the National Park Kopaonik - opportunities and challenges - Nonić Dragan; Šumarac Predrag; Ranković Nenad; Đorđević Ilija; Nedeljković Jelena (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2023)
The management of the National Park (NP) Kopaonik is entrusted to the Public Enterprise (PE) “NP Kopaonik”, which represents a delegated form of “state management” in the public sector. The paper aims to study the most important elements of the management organization of NP Kopaonik. Regulatory and institutional frameworks, internal organization and financing mechanisms for the management of NP Kopaonik were discussed. The purpose of the research is to determine the possibility of improving the organization and financing of NP Kopaonik towards sustainable management. Primary data was collected by conducting interviews with representatives of management and stakeholders. In terms of improving the internal organization of PE “NP Kopaonik”, it was proposed to form additional organizational units, i.e. services for visitor management, promotion, cooperation with the media and marketing, provision of tourist offers, preparation and implementation of projects and international cooperation, as well as the improvement of hunting and fishing. It was emphasized that these tasks are already performed within the PE “NP Kopaonik” but also that it is necessary to make certain changes in the organizational structure and strengthen personnel and financial capacities, which would affect the quality of these activities.